Invisibility in Visual and Material Culture
XX, 232 p. 19 illus., 13 illus. in color.
Keywords: The essays in Invisibility in Visual and Material Culture contribute pioneering and revelatory insights into the phenomenon of invisibility, forging new and multi-disciplinary approaches at the intersection of aesthetics, technology, representation and politics. Importantly, they acknowledge the complex interaction between invisibility and its opposite, visibility, arguing that the one cannot be fully grasped without the other. Considering these entanglements across different media forms, the chapters reveal that the invisible affects many cultural domains, from digital communication and operative images to the activism of social movements, as well as to identity, race, gender and class issues. Whether the subject is comic books, photographic provocations, biometric and brainwave sensing technologies, letters, or a cinematic diary, the analyses in this book engage critically and theoretically with the topic of invisibility and thus represent the first scholarly study to identifyits importance for the field of visual culture.